2014
DOI: 10.1016/j.ijpara.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a genetically modified Brugia malayi cysteine protease inhibitor-2 reduces adult parasite numbers and affects the fertility of female worms following a subcutaneous challenge of Mongolian gerbils (Meriones unguiculatus) with B. malayi infective larvae

Abstract: Vaccination of Mongolian gerbils with Brugia malayi cysteine protease inhibitor-2 in which the amino acid Asn66 was mutated to Lys66 (Bm-CPI-2M) resulted in reduced parasite numbers of 48.6% and 48.0 % at 42 and 90 days p.i. with B. malayi L3s. Fertility of female worms was also affected at 90 days p.i. In vitro killing of L3s observed in the presence of gerbil peritoneal exudate cells and anti-Bm-CPI-2M sera suggests antibody-dependent cell-mediated cytotoxicity as a putative protective mechanism. These obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Using a phage-display based cDNA expression library of the parasite, sera of EN subjects were screened to identify several potential vaccine antigens that recognized the protective antibodies (Gnanasekar et al 2004). Subsequent evaluation of these antigens especially as a multivalent formulation (r Bm HAT) gave the highest (92%) rate of protection in rodent models (Thirugnanam et al 2007; Samykutty et al 2010; Kalyanasundaram and Balumuri 2011; Dakshinamoorthy et al 2013a; Dakshinamoorthy et al 2013c; Arumugam et al 2014). However, the same vaccine with alum adjuvant gave only about 40% protection in rhesus macaques (Dakshinamoorthy et al 2014) and the immune response generated was predominantly a Th2 biased with little or no Th1 response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a phage-display based cDNA expression library of the parasite, sera of EN subjects were screened to identify several potential vaccine antigens that recognized the protective antibodies (Gnanasekar et al 2004). Subsequent evaluation of these antigens especially as a multivalent formulation (r Bm HAT) gave the highest (92%) rate of protection in rodent models (Thirugnanam et al 2007; Samykutty et al 2010; Kalyanasundaram and Balumuri 2011; Dakshinamoorthy et al 2013a; Dakshinamoorthy et al 2013c; Arumugam et al 2014). However, the same vaccine with alum adjuvant gave only about 40% protection in rhesus macaques (Dakshinamoorthy et al 2014) and the immune response generated was predominantly a Th2 biased with little or no Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for a more sustained approach such as a prophylactic vaccination to stop transmission and eliminate LF from the endemic areas (Dakshinamoorthy et al 2013c; Jambulingam et al 2016; Harris et al 2017). Our laboratory and others have identified several potential vaccine antigens that are shown to confer significant protection against challenge infections in experimental animals (Samykutty et al 2010; Dakshinamoorthy et al 2013b, Dakshinamoorthy et al 2013c; Arumugam et al 2014). One of our recent trials in non-human primates using a trivalent fusion protein vaccine (r Bm HAT) showed that approximately 40% protection could be achieved in vaccinated animals against a challenge infection (Dakshinamoorthy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When monitoring adult worm cultures, some studies also evaluate effects of potential antifilarial agents on worm fecundity by measuring the number of microfilariae released by adult female worms on a daily basis (134,138,146,148,153). Adult worms can also be dissected at the study endpoint to enable microscopic assessment of effects on embryogenesis with regard to both numbers of embryos and stages of embryo development (134,153,157).…”
Section: Filariaementioning
confidence: 99%
“…Filarial CPI-2 is an immunomodulatory protein that blocks the MHC class II antigen presentation pathway by inhibiting papain-like proteases and asparaginyl endopeptidase (Manoury et al, 2001). However, mutation of a key asparagine residue in CPI-2 ablates this activity (Murray et al, 2005), rendering the modified molecule a highly effective vaccine antigen (Arumugam et al, 2014;Babayan et al, 2012;Hess et al, 2014). Here, we compare the efficacy of mutated onchocystatin immunotherapy alone or in combination with a short oxytetracycline regimen against natural O. ochengi infection in Cameroonian cattle.…”
Section: Introductionmentioning
confidence: 99%